3D virtual reconstruction of the Kebara 2 Neandertal thorax. Issue 1 (December 2018) - Gómez-Olivencia, Asier; Barash, Alon; García-Martínez, Daniel; Arlegi, Mikel; Kramer, Patricia; Bastir, Markus; Been, Ella
Abstract The size and shape of the Neandertal thorax has been debated since the first discovery of Neandertal ribs more than 150 years ago, with workers proposing different interpretations ranging from a Neandertal thoracic morphology that is indistinguishable from modern humans, to one that was significantly different from them. Here, we provide a virtual 3D reconstruction of the thorax of the adult male Kebara 2 Neandertal. Our analyses reveal that the Kebara 2 thorax is significantly different but not larger from that of modern humans, wider in its lower segment, which parallels his wide bi-iliac breadth, and with a more invaginated vertebral column. Kinematic analyses show that rib cages that are wider in their lower segment produce greater overall size increments (respiratory capacity) during inspiration. We hypothesize that Neandertals may have had a subtle, but somewhat different breathing mechanism compared to modern humans. How different Neandertal morphology was from that of modern humans has been a subject of long debate. Here, the authors develop a 3D virtual reconstruction of the thorax of an adult male Neandertal, showing similar size to modern humans, yet with greater respiratory capacity due to its different shape.